Rare, Endemic and Medicinal Plants of Selected Sacred Groves in Chavakkad, Thrissur District, Kerala. - M.R., Deepa; Dharmapal, Sheema; Udayan, P.S. (Asian Journal of Biological and Life Sciences, 2016)
Sacred groves are the remnants of forest patches which is protected and conserved based on religious beliefs. It acts as repositories of many RET, medicinal and economically important plant species. An exploratory survey was conducted in some selected sacred groves of Chavakkad Taluk in Thrissur District namely Cherayi padinjakkara sarpakavu, Kanjiramthara kavu, Nariyampully kavu, Ullanatt raman moothapanicker vaka sarpakavu and Ullannur mana sarpakavu. There are 79 species of flowering plants in the grove distributed in 42 families comprising of 46.84 % trees, 15.19 % shrubs, 11.39 % herbs and 26.58 % climbers. Three species of palms Areca catechu L., Caryota urens L. and Cocos nucifera L. were found to occur in the groves. Caryota urens L., Dioscorea bulbifera L. and Pothos scandens L. were found to be distributed all over the grove. Out of these 79 plants 7 plants were Endemic, 7 Vulnerable and 3 plants coming under Lower risk near threatened in Kerala. All 79 plants are medicinal. Groves are rich in its floral and faunal wealth. This helps to increase the water table in surrounding areas and purifies air. This is beneficial for all organisms including human beings.
Keywords: Endemic; Medicinal plants; Rare; Sacred grove